34 A systematic literature review of the pre-hospital lessons identified following mass casualty deliberate bombing incidents. Issue 12 (23rd November 2017) - Cooke, Thomas; Chesters, Adam; Grier, Gareth
Abstract : Background: Since the end of World War II, there has been an emergence of explosives used amongst civilian populations resulting in mass-casualty incidents. The development of pre-hospital medical systems, worldwide, has resulted in an increased response at these incidents. However, information about the pre-hospital medical response is sparse and not collated. This review aimed to collect and appraise the literature on the pre-hospital management of mass-casualty bombing incidents. The primary objective was to identify and discuss the common themes highlighted as problems in the pre-hospital medical response. The secondary objectives reviewed the injury patterns in victims and psychological impacts on pre-hospital responders. Methods: A systematic literature search on the PubMed, SCOPUS and Web of Science databases took place. It included literature published from the 1 st of January 2000 to April 3rd 2017, with the last search performed on April 3rd 2017. Literature was included if it offered description, analysis, reflection or review of the bombing incidents. Results: 1345 articles were found, with 54 included in analysis. 13 mass-casualty bombing incidents were described. Two of these included marauding terrorist firearm attacks (MTFA). In the 11 bombing-only incidents the death of 592–642 people and injury of 3, 842–5229 more is described, with a further 301 deaths and 604 injuries from bombings with MTFA attacks. Quality appraisal showed a variation in reporting among incidents and a lack of uniform reporting. Conclusions: Functioning and reliable communication, alongside regular training exercises with other emergency services, is important in the pre-hospital response. This is aided through accurate triage, in a safe area, to ensure even casualty distribution. A visible and established command and control enables scenes to be led effectively. Access to suitable and adequate supplies of equipment fosters improvement in patient outcomes. Awareness of secondary devices, as well as chemical, radiological and nuclear exposure, is vital in ensuring responder safety. A variety of injury patterns was found. Finally, psychological complications and support systems amongst pre-hospital responders varied.